House of pain : new and selected essays - Gonzales, Laurence, 1947- (University of Arkansas Press, 2013)
This collection of essays shows us the sometimes hair-raising, sometimes heart-wrenching writing that the author has become known for. This book takes us from a maximum-security prison to a cancer ward, from a mental institution to the World Trade Center. Among the essays included is “Marion Prison,” a National Magazine Award finalist, with its intimate view inside the most maximum security prison in America. “House of Pain” takes the reader into the life of a brain surgeon at Chicago’s Cook County Hospital, a grim world that few ever see. “Rites of Spring,” another National Magazine Award finalist, follows Gonzales and his wife on their journey through cancer, not once, but twice. Other stories venture above the Arctic Circle, flying deep into the Alaskan wilderness among grizzly bears and trumpeter swans; explore aerobatics in high-performance aircraft; and eulogize Memphis and Miami as American cities that mourn their fates in uniquely different ways.